Loss of Control Eating and Health Indicators Over 6 Years in Adolescents Undergoing Metabolic and Bariatric Surgery. Issue 4 (23rd March 2021) - Goldschmidt, Andrea B.; Khoury, Jane C.; Mitchell, James E.; Jenkins, Todd M.; Bond, Dale S.; Zeller, Meg H.; Michalsky, Marc P.; Inge, Thomas H.
Abstract : Objectives: The aim of this study was to assess associations between loss of control (LOC) eating and health outcomes among adolescents undergoing metabolic and bariatric surgery. Methods: A total of 234 adolescents were studied before and up to 6 years after surgery in a prospective, observational cohort design. Adolescents provided self‐reports of LOC eating, pain severity, sleep quality, polycystic ovary syndrome, gastroesophageal reflux disease, and medication usage and objective measures of fasting glucose, serum insulin, glycohemoglobin A1c, cholesterol, triglycerides, and blood pressure. χ 2 tests, Wilcoxon rank sums, and generalized linear mixed models were used to assess concurrent and prospective associations between LOC eating and health indicators. Results: LOC eating presented in 32.5% of adolescents before surgery and was positively associated with sleep disturbances and psychiatric medication usage. After surgery, LOC eating presented in 7.9% to 14.6% of participants and was correlated with improved low‐ and high‐density lipoprotein cholesterol levels and greater back pain. LOC eating was inversely associated with low‐density lipoprotein cholesterol at the next consecutive time point. Conclusions: LOC eating was unexpectedly associated with improved low‐ and high‐density lipoprotein cholesterol in adolescents undergoing metabolic and bariatric surgery. Deleterious effects of LOC eating on obesity‐related health conditions, aside from back pain, were not detected. Metabolic and other weight‐independent health benefits of surgery may persist postoperatively despite LOC eating and associated weight regain.